2023
DOI: 10.1007/s11033-022-08170-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of long-range PCR protocol to prepare filaggrin exon 3 libraries for PacBio long-read sequencing

Abstract: Background The filaggrin (FLG) protein, encoded by the FLG gene, is an intermediate filament-associated protein that plays a crucial role in the terminal stages of human epidermal differentiation. Loss-of-function mutations in the FLG exon 3 have been associated with skin diseases. The identification of causative mutations is challenging, due to the high sequence homology within its exon 3 (12,753 bp), which includes 10 to 12 filaggrin tandem repeats. With this study we aimed to obtain the whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…14 Long-range PCR demonstrated that 15-kbp amplicons could be generated from the DNA extracts, indicating amenability to sequencing. 15,16 Improved yields and higher DNA integrity with Puregene compared with QIAamp have both been demonstrated before. [17][18][19] The difference between the two kits in respect of DNA yield was extensive, both in the initial study using 11 blocks per method and in the validation cohort.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…14 Long-range PCR demonstrated that 15-kbp amplicons could be generated from the DNA extracts, indicating amenability to sequencing. 15,16 Improved yields and higher DNA integrity with Puregene compared with QIAamp have both been demonstrated before. [17][18][19] The difference between the two kits in respect of DNA yield was extensive, both in the initial study using 11 blocks per method and in the validation cohort.…”
Section: Discussionmentioning
confidence: 80%
“…We numbered the bands such that each band number represented a band of distinct molecular mass that was unique to a tissue block, but which could be present in more than one homogenization of that tissue block. There were a total of 127 bands numbered [mean, 17.5 per block (range, [14][15][16][17][18][19][20][21][22]], of which 5.5 % were only detected in homogenization 2, 5.5% only in homogenization 3, and 3.1% only in homogenization 4. Most were present in all three homogenizations (73 % of the total, n=93), and the remainder were in two homogenizations only (Fig.…”
Section: Repeated Homogenizations Of Tissue Block Debris and Then Add...mentioning
confidence: 99%
“…We initially identified 5 children in this study with 2 or more FLG LoF variants according to the genotype calls based upon short-read sequencing (Table 2). To determine the chromosome phase of these variants and identify those children with compound heterozygous FLG LoF variants, we performed long-read sequencing on DNA following PCR enrichment of exon 3 as previously published (21). The analysis of these sequences validated 3 children with compound heterozygous FLG LoF variants (Figure 1, C-E, and Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Five individuals (out of 438) in this study were determined to have 2 or more heterozygous FLG LoF variants via short-read sequencing. To validate phase and genotype for these 5 samples, DNA from blood was extracted as described above, and a published protocol was used to PCR-amplify exon 3 for long-read sequencing (21). Briefly, the first PCR reaction used forward: 5′TGGGACAGTGATTATGTTGGAGA3′ and reverse: 5′AGGGTTATTTT-GAGCTCTTTGTGAA3′ primers to amplify a 12-kilobase region that was then amplified in a second nested PCR reaction with forward primer: 5′GGCGCAGACTGTCCATGGGT3′ and reverse primer: 5′TCG-GCAAATCCTGAAGGTAAGAGTC3′.…”
Section: Methodsmentioning
confidence: 99%
“…The SMRTbell library to sequence RPGR ORF15 was prepared following the PacBio protocol guidelines Procedure & Checklist-Preparing SMRTbell ® Libraries using PacBio ® Barcoded Universal Primers for Multiplexing Amplicons-Part Number 101-791-800 Version 02 (April 2020) [26]. All assays were performed as already described in our publication [27].…”
Section: Smrtbell Library Preparation and Tgs Sequencingmentioning
confidence: 99%